Alondra: new poinsettia hybrid for interiors - Canul Ku, Jaime; García Pérez Faustino; Barrios Gómez Edwin Javier; Rangel Estrada Sandra Eloísa; Ramírez Rojas Sergio Gavino; Osuna Canizalez Felipe de Jesús (Revista Mexicana de Ciencias Agrícolas, 2017)
The market for ornamental plants is dynamic. There is constant demand for new improved varieties. Faced with this situation since 2010 the poinsettia (Euphorbia pulcherrima Willd. Ex Klotzsch) breeding program was implemented in the Zacatepec Experimental Field of the Instituto Nacional de Investigaciones Forestales, Agrícolas y Pecuarias. Which allowed the generation of improved material called Alondra through the crosses between OAX14P4*MORFRN1015-9 conducted in 2010. The hybrid progeny was established by seed in 2011 and the selection of the best individuals was performed in 2012. For the following four years they were evaluated with cooperating producers, together with other hybrids, of which this cross was the most outstanding. Alondra shows oval-shaped leaves with a cuneiform base, the main nerve of the bundle is green and red, the leaf lobes are shallow, the petiole is long and intense green colored in the bundle. The bracts are red and elliptical shaped. The width of the top is medium with yellow small ciatio glands, without deformation. This new poinsettia material has germplasm of national origin, it was generated and developed in the area where the greatest commercial production is carried out, consequently, it is an adapted material and does not show problems of bracts pigmentation, which is the commercial and aesthetic aspect. It represents an option to diversify the supply in the national market since its behavior is similar to the one of commercial varieties.